Isolation and Classification of Green Alga Stigeoclonium attenuatum and Evaluation of its Ability to Prepare Zinc Oxide Nanoflakes for Methylene Blue Photodegradation by Sunlight - Marwa A. Aubaeed; Amjed Mirza Oda; Emad Y.A. AL-Sultan (مجلة بغداد للعلوم)
Algae have been used in different applications in various fields such as the pharmaceutical industry, environmental treatments, and biotechnology. Studies show that the preparation of nanoparticles by a green synthesis method is a promising solution to many medical and environmental issues. In the current study, the green alga Stigeoclonium attenuatum (Hazen) F.S. Collins 1909 was isolated and identified from the Al-Hillah River (Governorate of Babylon) in the middle of Iraq. The green synthesis by the aqueous extract of algae was used to prepare the nanoflakes of ZnO. Nanoflakes of ZnO are characterized by X-Ray diffraction (XRD) and scanning electron microscope (SEM) with flakes shape and dimensions ranging between 200-500 nm and thickness between 20-23 nm. And this study comprises a test of ZnO nanoflakes efficiency as a photocatalyst factor, thus experiments set of an aqueous solution of methylene blue with ZnO nanoflakes and exposed to sunlight have been conducted. The absorbance of methylene blue at 660 nm reduces over time and almost vanishes between 60-120 minutes. Consequently, it is obvious that in the presence of sunlight, pristine ZnO nanoflakes are photocatalytically active with a degradation efficiency of 97%. Furthermore, the antibacterial activity of ZnO nanoflakes that were prepared by aqueous extract of algae was evaluated against some resistant strains of bacteria Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Streptococcus sp. and the antibacterial activity of NPs rises as concentration increases 50, 100, and 150 μg/ml.